POSTPARTUM HOME CARE NEEDS AND MIDWIVES’ READINESS: A CROSS-SECTIONAL STUDY IN LOMBOK, INDONESIA - Yopi Suryatim Pratiwi; Yesvi Zulfiana; Siskha Maya Herlina; Sri Handayani (Universitas Kusuma Husada Surakarta, 2026)
Background: The postpartum period is a critical phase requiring intensive monitoring, as postpartum complications remain a leading cause of maternal mortality, while the coverage of home-based care services in Indonesia remains limited. This study aimed to assess the need for postpartum home care services from the perspectives of postpartum mothers and midwives.Methods: A quantitative descriptive study with a cross-sectional design and purposive sampling was conducted, involving 100 postpartum mothers and 40 midwives across four regions in Lombok, Indonesia. Data were collected using structured 4-point Likert-scale questionnaires that had been tested for validity and reliability.Results: All postpartum mothers (100%) had never received home-based care, with a high level of need (mean score 3.3/4). The highest demand was for perineal/wound care (96%). Midwives demonstrated high readiness (mean score 2.9/4) but faced major constraints: limited portable medical equipment (87.5%), insufficient financial incentives (80%), and heavy workloads (75%). None of the midwives had received specific home care training. Both groups supported the development of smartphone applications with live chat and video education features (scores >3.2), but rejected the complete substitution of in-person visits (mothers scored 2.9/4; midwives 2.5/4).Conclusion: This study is the first quantitative study in Indonesia to simultaneously integrate the perspectives of postpartum mothers and midwives, providing empirical evidence that digital technology serves as a complement, not a substitute, for in-person visits, thereby recommending a hybrid model (home visits, telehealth, and digital education) as the ideal approach. A gap exists between the high demand for home-based care among postpartum mothers and midwives' implementation capacity, which is constrained by systemic factors. National standards, infrastructure strengthening, incentives, training, and integrated technological support are essential to establish effective and sustainable postpartum home care services.